2015
DOI: 10.1007/s11104-015-2379-7
|View full text |Cite
|
Sign up to set email alerts
|

Next generation shovelomics: set up a tent and REST

Abstract: Aims Root system architecture traits (RSAT) are crucial for crop productivity, especially under drought and low soil fertility. The Bshovelomics^method of field excavation of mature root crowns followed by manual phenotyping enables a relatively high throughput as needed for breeding and quantitative genetics. We aimed to develop a new sampling protocol in combination with digital imaging and new software. Methods Sampled rootstocks were split lengthwise, photographed under controlled illumination in an imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 54 publications
3
105
0
Order By: Relevance
“…Shallow rooting has been proposed to increase phosphorus uptake efficiency, while deep rooting have been proposed as beneficial for nitrate and water uptake (Wasson et al, 2012;Lynch, 2013;Trachsel et al, 2013). However, accurate determination of angles is often possible only in 2D systems or, after excavation, for relatively stiff roots (Trachsel et al, 2010;Colombi et al, 2015). Our NMRooting approach calculated branching angles of every root of a single plant in 3D (for details, see "Materials and Methods").…”
Section: Discussionmentioning
confidence: 99%
“…Shallow rooting has been proposed to increase phosphorus uptake efficiency, while deep rooting have been proposed as beneficial for nitrate and water uptake (Wasson et al, 2012;Lynch, 2013;Trachsel et al, 2013). However, accurate determination of angles is often possible only in 2D systems or, after excavation, for relatively stiff roots (Trachsel et al, 2010;Colombi et al, 2015). Our NMRooting approach calculated branching angles of every root of a single plant in 3D (for details, see "Materials and Methods").…”
Section: Discussionmentioning
confidence: 99%
“…were recently further optimized with regards to the sampling strategy and software solution 112 (Colombi et al, 2015) where instead of sampling the whole root system, only half of the root 113 system is sampled. This method enhanced on the one hand the transportation and cleaning 114 process and enabled on the other hand a better insight into the root system without excessive 115 overlapping of the roots on the image.…”
Section: Spells 47mentioning
confidence: 99%
“…In common bean instead, a high number of basal roots in the top soil improved phosphorus uptake and plant vigor in low phosphorus soils (Miguel et al, 2013). A major advantage of root system architectural traits and root numbers in particular is that they can be assessed in large diversity panels under field conditions at high throughput rates (Trachsel et al, 2011; Colombi et al, 2015; Burridge et al, 2016). The quantification of root dry weight or length instead is much more laborious and not feasible under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The quantification of root dry weight or length instead is much more laborious and not feasible under field conditions. The heritability of root numbers was reported to be relatively high in a wide range of crop species (Wilcox and Farmer, 1968; Bucksch et al, 2014; Colombi et al, 2015; Li et al, 2015; Richard et al, 2015; Burridge et al, 2016). Besides increasing awareness about the importance of roots for crop production, it has been suggested that holistic phenotyping approaches are needed to understand plant responses to abiotic stress.…”
Section: Introductionmentioning
confidence: 99%